Drosophila Pipe protein activity in the ovary and the embryonic salivary gland does not require heparan sulfate glycosaminoglycans. - Zhu, X.; Sen, J.; Stevens, L.; Goltz, J.S.; Stein, D. (Development, 2005)
The Drosophila pipe gene encodes ten related proteins that exhibit amino acid sequence similarity to vertebrate heparan sulfate 2-O-sulfotransferase. One of the Pipe isoforms, which is expressed in the ventral follicular epithelium, is a key determinant of embryonic dorsoventral polarity, suggesting that Pipe-mediated sulfation of a heparan sulfate proteoglycan provides a spatial cue for dorsoventral axis formation. We used several approaches to investigate this possibility in the work described here. We determined the nucleotide alterations in 11 different pipe alleles. Ten of the mutations specifically affect the pipe isoform that is expressed in the ovary. Among these ten mutations, two alter an amino acid in the putative binding site for 3'-phosphoadenosine 5'-phosphosulfate, the universal sulfate donor. Using Alcian Blue, a histochemical stain that detects sulfated glycans, we observed a novel, pipe-dependent macromolecule in the embryonic salivary glands. Genes known to participate in the formation of heparan sulfate in Drosophila are not required for the production of this material. To investigate whether a heparan sulfate proteoglycan is involved in pipe function in dorsoventral patterning, we generated females carrying follicle cell clones mutant for heparan sulfate synthesis-related genes. Embryos from follicles with mutant clones did not exhibit a dorsalized phenotype. Taken together, our data provide evidence that Pipe acts as a sulfotransferase, but argue against the hypothesis that the target of Pipe is a heparan sulfate glycosaminoglycan.